MEMBINCANG PEREMPUAN BERSAMA PIERRE BOURDIEU - Esha, Muhammad In'am (EGALITA, 2007)
Woman issue has been an interesting topic of discussion. It is undisputable that women problem becomes celebrity at the end of 20th century and this 21st century. This piece of writing tries to look deeply at gender problems, one of discussions about women, in one French sociologistâ€™s perspective. From this discussion, it can be revealed that gender struggle is one of strategic steps for the struggle of social class of women. The mechanism of this sort of struggle should put habituÃ©s, arena and capital into account.